RECOVERY OF ABUTMENT TEETH AND CALIBRATING THE EDENTULOUS SPACES IN VIEW OF THE SUBSEQUENT PROSTHESES - Andreea-Ionela Gradinariu; Gabriel Rotundu; Codrin Ionut Alexandru (Romanian Dental Association for Education, 2022)
The aim of the study was to debate and analyze the cases exposed in various magazines and specialized sites by referring to preprotective adjustments so necessary to obtain a prosthetic potential space of desired sizes. Interdisciplinary collaborations in dental medicine make it possible to treat the complex, successful treatment of various abnormalities leading otherwise to restore the functions of the stomatgnate system. In recent practice, focus on functionality and aesthetics, without compromise. It can be seen as the Prosthetician will request orthodontic, surgical and periodontal help to achieve exceptional results. Result Clinical analysis should be associated with the paraclinical, the existence of current scanning and interpretation methods by facilitating exceptional results to the recovery of poles into the calibration of the edient space for subsequent prostheses.